Development of electro-active polymer (EAP) for biomedical application - Sim, Deborah Lay Peng. (2009)
Electroactive polymers (EAP) are widely used in many areas, such as actuators, sensors and transducers. Among the different type of electronic EAP, PVDF-TrFE based ferroelectric electrictive polymer gain much attention due to their high strain level and high elastic energy density. Recently, the use of EAP as artificial muscles has gained significant attention, however few researchers concentrated on the study of PVDF-TrFE for biomedical application. In this thesis, we will focus on the development and optimizing of PVDF-TrFE on its electromechanical response.